Advancing sustainable development goals through public health service learning: Avanzando metas de desarrollo sostenible mediante el aprendizaje del servicio de salud pública - Perez, Miguel A. (2019)
Objective: To discuss the development and implementation of a service learning experience designed to improve the health status of vulnerable populations in a middle-income country through the implementation of science-based programs designed to address the World Health Organization’s “Ten Threats to Global Health.” Methods: Describes the pragmatic development of a service learning experience designed to provide hands-on experiences to public health and medical students as they develop into professionals in high-middle-and low-income countries. Results: “Exploring Global Social Determinants of Health in the Dominican Republic,” originally designed as an observational experience of social determinants of health, has evolved into an experiential learning experience designed to assist students in the application of their public health knowledge and experience. Conclusion: Public health professionals, including those in training, have a responsibility to implement actions designed to improve the health status of populations around the world. Service learning programs such as “Exploring Global Social Determinants of Health in the Dominican Republic,” provide those hands-on opportunities.